Productivity Improvement of premium Quality Rice Through Fertilizer Management in The Haor Areas (Bangladesh Agronomy Journal, 2017)
The experiment was conducted at the farmers fields of two villages namely Bahadurpur and Noagaonat Sadar upazilla and Daskin Sunamganj, respectively under Dekhar haor of Sunamganj district during the period from November, 2015 to May 2016 to find out the effect of variety and fertilizer on the, yield and yield contributing characters of premium quality rice in haor area. Two varieties (BRRI dhan50 and BRRI dhan63) and three fertilizer treatments (Farmers practice, FRG and Soil test based fertilizers) were included in the experiment. The experiment was laid out in a Factorial Randomized Complete Block Design (RCBD) with three dispersed replications. Tillers hill-1 was significantly affected due to different varieties at 60, 75, 90 DAT (Days after Trasplnting) and at harvest but significantly varied due to different fertilizers application at 30 and 60 DAT interaction at 45 and 60 DAT. The maximum grain and straw yield of 3.86 and 5.67 t ha1, respectively was produced from the BRRI dhan63. Though the grain yield was identical but lower yield in the STB and maximum in farmers practice due to higher fertilizer. practices.Bangladesh Agron. J. 2016 19(2): 139-143